The closing door of climate targets - Stocker T F (Science, 2013)
The linear relationship between cumulative carbon emissions and global climate warming implies that as mitigation is delayed, climate targets become unachievable.
Source Year: 2012
Keywords: Carbon emission; Global climate warming